1972
DOI: 10.1002/bjs.1800590818
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous rupture of the oesophagus. Avoidance of postoperative morbidity

Abstract: SUMMARYTwelve cases of 'spontaneous rupture' of the oesophagus occurring over a period of 20 years (195 1-71) are reviewed. The principal clinical and radiological features are described and the factors concerned in the pathogenesis of this condition are discussed. Although the mortality rate in this study was low (8 per cent) the incidence of severe postoperative complications was considerable, occurring in 10 of the 11 operative survivors. The importance of early diagnosis and adequate surgical treatment in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1973
1973
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…The visible muscle split is usually shorter than the mucosal tear. Keighley and his colleagues showed that the muscle split was 2 cm shorter in the 7 cases in whom accurate measurements were taken (Keighley et al, 1972). Others have made the same observation.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…The visible muscle split is usually shorter than the mucosal tear. Keighley and his colleagues showed that the muscle split was 2 cm shorter in the 7 cases in whom accurate measurements were taken (Keighley et al, 1972). Others have made the same observation.…”
Section: Resultsmentioning
confidence: 71%
“…Both posteroanterior and lateral views should be obtained. When the topic was reviewed by Toghill et al in 1968, air had never been shown below the diaphragms, but this has now been reported by Bruno et al (1963), Keighley et al (1972) and Thornley and Wallwork (1 978). Pneumopericardium was reported by Mansour and Teaford (1973) but the case they described had previously undergone oesophagogastrectomy for a benign stricture of the lower oesophagus and subsequent fundic patch oesophagoplasty for recurrent stricture, 14 months before final presentation with oesophageal rupture into the pericardium.…”
Section: Investigationsmentioning
confidence: 85%
“…The symptoms can be easily misdiagnosed as dissecting aneurysm, myocardial infarction, pulmonary embolism, aspiration pneumonia, lung abscess, or ruptured subphrenic abscess (12). Keighley et al reported that the rate of diagnostic error is as high as 50% (13).…”
Section: Discussionmentioning
confidence: 99%
“…However, early diagnosis is sometimes difficult due to the non-specific symptoms, and the condition is sometimes misdiagnosed as arterial dissection, myocardial infarction, pulmonary infarction, or aspiration pneumonia 3) . The rate of correct diagnosis at the time of initial examination is reported to be low, at 30-50% 8,9) . The rupture was misdiagnosed initially in 4 of our 10 patients as pneumonia (1 patient), gastric ulcer (1 patient), cholecystitis (1 patient), and epigastric pain (1 patient).…”
Section: Discussionmentioning
confidence: 99%